Strange Uncivil: Mapping Patterns of Online Incivilities in the 2018 Brazilian Elections: Mapeo de patrones de incivilidad en línea en las elecciones brasileñas de 2018 (Gestão & Regionalidade, 2024)
The purpose of this article is to map and analyze patterns of incivility as a phenomenon unleashed on online social networks, on Facebook pages that expressed support for the right and far right in the 2018 elections, a context marked by polarization and aggressiveness in Brazil. We conducted a qualitative research on fifteen Facebook webpages in the State of Minas Gerais, and the empirical material was submitted to content analysis. The results point to the presence of strange uncivil in the dissemination and validation of incivility speeches online. The article contributes to the understanding of how social networks, specifically Facebook, can foster incivility discourses, bringing empirical knowledge about online incivility in the Brazilian political context of right and far right, stimulating reflections on uncivil practices, their specificities and its possible consequences in the organizational and social context, which also makes use of virtual space.
Keywords: Uncivil. Facebook. Far right.